Unraveling Self‐Doping Effects in Thermoelectric TiNiSn Half‐Heusler Compounds by Combined Theory and High‐Throughput Experiments. (29th December 2015) - Wambach, Matthias; Stern, Robin; Bhattacharya, Sandip; Ziolkowski, Pawel; Müller, Eckhard; Madsen, Georg K.H.; Ludwig, Alfred
Abstract : The control of the carrier concentration is a key topic in the optimization of the thermoelectric power factor. It depends intricately on the defect chemistry of a host phase (here: TiNiSn) and the boundary conditions set by competing phases. The large impact of a slight off‐stoichiometry in the intermetallic half‐Heusler phase TiNiSn makes combinatorial techniques ideally suited for systematic optimization of its thermoelectric performance. In this work, computational thermochemistry, combinatorial synthesis, and high‐throughput characterization are combined to obtain a complete map of the thermoelectric power factor for the Ti–Ni–Sn system. The role of the chemical potential of the constituents in determining the detailed nonstoichiometric composition of the intermetallic half‐Heusler phase TiNiSn is elucidated. This work not only confirms the assumption of a large phase‐width in terms of Ni surplus but also demonstrates that TiNiSn phases with a relatively large Ti surplus can be produced. This can serve as a new route for achieving high carrier concentrations by self‐doping in the ternary system Ti–Ni–Sn. The defect thermochemistry calculations for the carrier concentration are in excellent agreement with the experimental results. The findings of this work suggest new ways of improving the thermoelectric performance of half‐Heusler phases such as TiNiSn. Abstract : Thermoelectric performance improvement of off‐stoichiometric TiNiSn half‐Heusler compounds is investigated by means of theoretical calculations, combinatorial sputtering, and high‐throughput characterization. The results suggest that a Ti‐surplus and Ni‐deficiency improve the thermoelectric power factor significantly. The suitability of the high‐throughput approach to investigate and improve on thermoelectric material systems is substantiated.